Determination of olivine cooling rates from metal-cation ordering - Redfern, S; Henderson, C; Wood, B; Harrison, R; Knight, K (1996)
The mineral olivine - (Fe,Mg,Mn)2SiO4 - is the dominant phase in the Earth's upper mantle, and is also present in a wide range of igneous rocks. Metal cations in olivine crystals are partitioned between two structurally distinct octahedral sites, a property which could in principle be used to obtain important information regarding the thermal history of the host rock. But attempts to establish the temperature and pressure dependence of cation ordering, mainly from the room-temperature structures of samples that have been annealed and quenched1-3, have yielded contradictory information. In fact, recent studies have shown that considerable re-ordering occurs during the quenching process4,5, and thus cation ordering is unlikely to be representative of high- temperature equilibration. Here we present a new model of the thermodynamics and kinetics of metal partitioning in olivine, derived from in situ neutron-diffraction measurements of cation ordering in the synthetic olivine (Fe0.5Mn0.5)2SiO4. Our results suggest that the room-temperature structure of a quenched olivine reflects the rate at which the mineral cooled. The extension of this approach to common rock-forming olivines should provide a valuable 'geospeedometer' for determining the cooling rates of rocks that have cooled relatively rapidly.